Prognostic Impact of Cytoreductive Nephrectomy in Patients with Metastatic Renal Cell Carcinoma: Data from a Large Population-Based Database - Alnimer, Yanal; Qasrawi, Ayman; Yan, Donglin; Wang, Peng (Urology Journal, 2021)
Purpose: Cytoreductive nephrectomy (CN) was considered a well-established treatment modality for patients with metastatic renal cell carcinoma (RCC) in the interferon era. However, its role after the introduction of multiple targeted therapies is less well established. Herein, We evaluated the effect of CN on overall survival (OS) on patients with RCC who were identified through the Surveillance, Epidemiology, and End Results database (SEER). Materials and Methods: A total of 5,483 patients with metastatic RCC were identified from 2010 to 2016 using the SEER database. Factors pertaining to the following variables were collected: presence or absence of CN; age; gender; grade; status of metastasis to bone, liver, lung and brain; tumor stage; nodal status; histological subtypes; and chemotherapy status. Subjects who had CN were matched with those who did not in all previously mentioned covariates using inverse probability weighting. These weights were then used in adjusted Cox regression models to report doubly robust estimates. Results: CN was associated with 67% reduction in the hazards of death. Advanced T-stage, N1 disease, advanced tumor grade, non-clear histology and metastasis to bone, liver, lung or brain are independent risk factors for death. Patients with T4 disease benefited less of CN compared to those with T1 disease, while higher number of metastatic sites didn’t predict worse outcome among those who had CN. Conclusion: CN could provide a survival advantage in favorable risk patients with RCC in the era of targeted therapy.